Self-Actualization of Preschoolers Through Role play In The Classroom - Ika Candra Destiyanti; Dini Okti Nuraini; Jajat Imanudin (Jurnal Fakultas Keguruan & Ilmu Pendidikan Kuningan, 2023)
A form of early childhood self-actualization into a happy learner is the urgency of the preschool teacher realizing his professionalism. How concrete steps can be given by preschool teachers in their implementation is a form of teacher learning innovation in the classroom. This research is qualitative research with observation and interview techniques on how preschool teachers' efforts implement classroom teaching strategies in order to realize students' self-actualization in the classroom. The results of the research explain that students' ability to socialize and be able to cope with their environment is the main factor in self-accounting of preschool students in the classroom.